STUDI PENGARUH BEBAN BERLEBIHAN TERHADAP PENGURANGAN UMUR PERKERASAN JALAN - Bumulo, Nasir; Djau, Rahman Abdul; Dunda, Pabowo (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study aims to determine the effect of the age of the road pavement that is passed by overloaded vehicles and the factors that influence road pavement damage to the design life using the Bina Marga 2022 component analysis method. Data collection techniques are carried out by collecting primary data and secondary data. Primary data collection was carried out by observing directly in the field, while secondary data collection was road geometric data and existing road pavement thickness obtained from the relevant agencies/agencies, in this case the Land Transportation Management Center for Region XXI Gorontalo Province and the PUPR Service for Highways. To be able to determine the age of the pavement and the factors that influence the damage to the pavement, an analysis of the data is carried out, including: average daily traffic data, vehicle axle load configurations, comparison between the damaged power by standard axle loads, design traffic values on lanes. cross section, cumulative ESAL value and pavement life. Based on the results of research on road damage analysis due to road overload loads on the Botu Office Access Road Section, it can be concluded that based on the traffic design analysis (ESAL) under normal conditions, the remaining life of the pavement is estimated to end in the 10th year since the research. traffic of 5% there is a reduction in the age of 1 year from the design age of 10 years, as well as with an increase in traffic of 10% and at a traffic increase of 15% there is a reduction of 2 years from the design age of 10 years